Design Principles and Human Factors in Modern Operating Rooms: Impact of Layout, Robotic Integration and Work-Related Stress - Cormio, Laura; Cormio, Luigi; Cannella, Cristian (British Journal of Healthcare and Medical Research, 2026)
The operating room (OR) is a high-risk clinical environment in which spatial configuration, technological integration, and human performance interact to influence surgical safety. The rapid expansion of robotic-assisted surgery (RAS) has significantly transformed traditional OR design requirements, introducing increased equipment density, altered team positioning, and modified communication patterns. Empirical evidence indicates that suboptimal layout, inefficient zoning, and workspace constraints contribute to flow disruptions, cognitive workload, and work-related stress. Robotic systems amplify these vulnerabilities by increasing technological footprint and docking complexity. Flow disruptions, particularly within transitional zones, represent persistent latent conditions affecting workflow continuity. Stress in surgical settings has been associated with impaired communication and performance, suggesting that environmental inefficiencies may indirectly influence safety outcomes. This review synthesizes current evidence on OR spatial configuration, equipment integration, workflow interruptions, and stress in robotic surgery. The findings support a systems-based, human-centered approach to operating room design to optimize efficiency, resilience, and team performance in technologically advanced surgical environments.